Career facilitators and obstacles of Australian football development coaches. Issue 2 (April 2016) - Dawson, Andrew; Dioth, Talei; Gastin, Paul B
Career development is considered integral to the success of individuals, organisations and professions. Coaches play a vital role in the success of sport, yet little is known about their career development. Despite the advances in career development for athletes, there has been very little scholarly attention, nor resources provided for coach career development, especially for coaches working outside elite and professional sport. This pilot study explored the career development facilitators and obstacles of junior development Australian football coaches. Semi-structured interviews were used to collect data on the career development of six practicing junior development Australian football coaches. These six (of only 12 employed) coaches worked in the main elite junior development league for Australian football, the Transport Accident Commission Cup. The themes that emerged from the data revealed that the career development of junior development Australian football coaches was facilitated first by their high motivation to coach because of their enjoyment of seeing young players develop and transition into the elite competition. The second facilitator was the coach's awareness of their career development needs and their willingness to do their own career development despite limited opportunity, guidance or support. The key obstacles to Transport Accident Commission Cup coach career development included a lack of opportunity to spend time at elite clubs to observe and interact with elite coaches; a lack of time due to having a non-coaching job to financially support their coaching work and their family as well; the high demands of the coaching role had a negative impact on their work – life balance and often conflicted with time they would rather spend with their families; and finally, the lack of institutional support for coaches who were asked to work long hours for low wages and little reward despite their vital role in the elite player development pathway for the Australian Football League. This research suggests that junior development Australian football coaches have a clear understanding of their role and how it changes as their career develops; however, the coaches are limited by external forces in their career development. Junior development Australian football coaches are vital for Australian Football League development; however, there is disconnection between Australian Football League goals and their capacity to nurture elite athletes into the sport's system due to part-time coaching roles, limited resources and few opportunities for coaches to develop their careers.